Apatite oxynitride phosphor (Mg, Y)5Si3(O, N)13:Ce3+, Mn2+: A single‐phased host with solar‐like and efficient emission. Issue 5 (11th January 2023) - Wu, Yanzheng; Li, Weiqiang; Zheng, Yifan; Xu, Yiqin; Wen, Dawei; Molokeev, Maxim S.; Pan, Zaifa
Abstract: During pursuing high color rendering index for full‐color‐emitting phosphor, low quantum efficiency (QE) is usually accompanying. We intend to elevate the luminescence efficiency when realizing a solar‐like spectra distribution, by constructing apatite structure oxynitride, inheriting high covalence and rigidity from oxynitride, and suitable multiple cation sites from oxyapatite compounds. Full‐color‐emitting apatite structure oxynitride phosphor (Mg, Y)5 Si3 (O, N)13 :Ce 3+, Mn 2+ has been prepared, and the crystal sites' occupancies of activators in this host were favorable for white emission. (Mg, Y)5 Si3 (O, N)13 :Ce 3+, Mn 2+ phosphor shows whole visible light with emission wavelength ranging from 370 to 750 nm, matching the spectra of sunlight quite well. The fabricated white light‐emitting diode lamp demonstrated the distinctive overall performance of QE and chromaticity properties ( R a and R 9 ). Furthermore, correlated color temperature is tunable from cool nature to warm white. The obtained lamp possesses the feature of less blue light hazard and high saturation of red degree, compared with the commercial YAG‐based lamp.